Adsorption of Organic Pollutants in Wastewater using Solid Phase Extraction Absorbent from Agro-Waste - Wan Norfazilah, Wan Ismail; Dzul Iskandar, Muhammad Fauzi; Nurlin, Abu Samah (Enviro Research Publishers, 2019)
A rapid solid phase extraction (SPE) combined with gas chromatography equipped with mass spectrometry (GC-MS) method was developed and validated for the determination of acenaphthylene, acenaphthene and naphthalene in wastewater sample collected from petroleum industry’s drainage. Important SPE parameters, namely absorbent amount, sample volume, type of elution solvent and its volume were optimized. The optimum parameters obtained are: 200 mg silica nano-powder, 2.0 mL sample volume and 2.0 mL n-hexane as elution solvent. The method showed good linearity in the range of 0.1-10.0 mg/L with satisfactory limit of detection (≤1.0 mg/L) and limit of quantitation (≤3.2 mg/L) under the optimized conditions. Good relative recoveries (94.7-99.9%) and intra- and inter-day precisions (≤2.8%, n=3) for acenaphthene, acenaphthylene and naphthalene were obtained. Toxicity study has revealed that it is a non-toxic absorbent and safe to be used for the removal of organic pollutants in water which is advantageous for routine wastewater analysis.